CARDIOVASCULAR RISK FACTORS AND IN-HOSPITAL MORTALITY IN 1258 CASES OF CORONARY ARTERY BYPASS SURGERY IN TEHRAN HEART CENTER - M Mandegar; M Marzban; A Lebaschi; P Ghaboussi; A Alai-Alamooti; A Ardalan (Acta Medica Iranica, 2008)
Coronary artery bypass grafting (CABG) surgery is being performed increasingly in Iran. So far, no large-scale report has described characteristics and risk factor profile and in-hospital mortality of patients undergoing this procedure in Iran. We conducted this study to address these topics in order to help clarify Iran's current state of CABG and to provide assistance in planning combat against coronary artery disease based on frequency of major risk factors. Patients who underwent isolated, first-time, elective, on-pump (conventional) CABG in a cardiac surgery center in Tehran were prospectively studied from September 2004 and March 2005. Demographic data, risk factor profile and discharge status for each patient were recorded. There were 1258 patients, 937 men (74.5%) and 321 women (25.5%). The mean age was 58.7 years (range 28 to 81); 133 patients (10.6%) were 70 years old or older. Mean body mass index (BMI) was 27.01 and 42.2% of the patients were smokers, 39.4% were hypertensive, and 27.6% had diabetes. Family history was positive in 40.3%. Congestive heart failure was found in 26.6%. New York Heart Association functional class III or IV was observed in 52.8% of patients. Single-vessel, two-vessel, and multi-vessel disease was found in 4.2%, 21.1%, and 74.7% of patients, respectively. Left main was involved in 9.8% and 14.4% had ejection fraction < 35%. The in-hospital mortality was 1.5%, mainly due to cardiac causes. This study indicates significant prevalence of major cardiovascular risk factors in Iranian CABG patients. In-hospital mortality of primary isolated CABG in Iran is similar to reported rates.